Eye tracking system - Cheng, Jing. (2011)
This report is a summary of the project of designing and developing an eye tracking system as one of the research fields of human-computer interaction (HCI). This system tracks the human eye ball movement through a video camera by using a computer program written in C++ language with the utilization of CAMSHIFT algorithm and OpenCV library.